Study of a bounded Coulomb potential - Ateser, Engin; Ciftci, Hakan; Yalcin, Zeynel (IOP PUBLISHING LTD, 2009)
In this paper, we have studied a new bounded Coulombic potential for the Schrodinger equation with the asymptotic iteration method (AIM). We have calculated energy eigenvalues for different potential parameters.
Keywords: ASYMPTOTIC ITERATION METHOD; ANGULAR SPHEROIDAL EIGENVALUES; SOLVABLE MATRIX MODELS; SCHRODINGER-EQUATION; DIFFERENTIAL-OPERATORS; ANHARMONIC-OSCILLATORS; PERTURBATION-THEORY; LIE-ALGEBRAS; EIGENENERGIES; SYSTEMS; Physics